Moderate and Deep Hypothermic Circulatory Arrest Have Comparable Effects on Severe Systemic Inflammatory Response Syndrome After Total Aortic Arch Replacement in Patients With Type A Aortic Dissection - Du, Yingjie; Fang, Zhongrong; Sun, Yanhua; Zhang, Congya; Lei, Guiyu; Chen, Yimeng; Yang, Lijing; Yang, Xiying; Li, Jun; Wang, Guyan (Frontiers in Surgery, 2021)
Background: The objective of this study was to compare the incidence of severe systemic inflammatory response syndrome (sSIRS) after total aortic arch replacement between patients who underwent moderate hypothermic circulatory arrest (MHCA) and those who underwent deep hypothermic circulatory arrest (DHCA). Methods: At Fuwai Hospital, 600 patients who underwent total aortic arch replacement with MHCA or DHCA from January 2013 to December 2016 were consecutively enrolled and divided into DHCA (14.1-20.0°C) and MHCA (20.1-28.0°C) groups. Preliminary statistical analysis revealed that some baseline indicators differed between the two groups; therefore, propensity score matching (PSM) was used to balance the covariates. Postoperative sSIRS as the primary outcome was compared between the groups both before and after PSM. Results: A total of 275 (45.8%) patients underwent MHCA, and 325 (54.2%) patients underwent DHCA. After PSM analysis, a total of 191 matched pairs were obtained. The overall incidence of sSIRS was 27.3%. There was no significant difference in postoperative sSIRS between the MHCA group and the DHCA group in either the overall cohort or the PSM cohort (no-PSM: P = 0.188; PSM: P = 0.416); however, postoperative sSIRS was increased by approximately 4% in the DHCA group compared with the MHCA group in both the no-PSM and PSM cohorts (no-PSM: 29.5% vs. 24.7%; PSM: 29.3% vs. 25.1%). Both before and after PSM, the rates of gastrointestinal hemorrhage and pulmonary infection and postoperative length of stay were signiﬁcantly increased in the DHCA group compared with the MHCA group (P < 0.05), and the remaining secondary outcomes were not significantly different between the groups. Conclusions: MHCA and DHCA are associated with comparable incidences of sSIRS in patients following total aortic arch replacement for type A aortic dissection. However, the MHCA group had a shorter cardiopulmonary bypass time, a shorter postoperative length of stay and lower pulmonary infection and gastrointestinal hemorrhage rates than the DHCA group. We cautiously recommend the use of MHCA for most total arch replacements in patients with type A aortic dissection.